(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Colorectal cancer is the third most frequent type of cancer in the world in both sexes, beginning in the large intestine and extending to the lower part of the digestive system. The most important risk factor is a family history of colon and rectal cancer and a genetic predisposition to developing chronic bowel diseases, in addition to a diet based on animal fats, as well as excessive alcohol consumption and smoking. Only 90% of polyps are easily found through colonoscopy, which highlights the importance of screening through colonoscopy, especially in patients aged 50 and over. When identified early, this pathology has a good prognosis. Aim: To demonstrate the importance of colonoscopy as a screening test for better colon cancer prognosis. Methods: Information was collected from a medical case that occurred at the Santa Casa da Misericórdia in Presidente Prudente, and its medical records. Results: Surgical treatment remains the best option. For tumors of the cecum and ascending colon, right colectomy and resection of a small segment of the distal ileum and right hemicolectomy are recommended. This approach is advantageous for patients with compromised lymph nodes, but its effectiveness seems doubtful for T3 or T4 with negative lymph nodes. Conclusion: Successful treatment of colon cancer is a multidisciplinary effort, with surgical resection being the most indicated, in combination with adjuvant chemotherapy in certain cases, and early diagnosis of patients being important for a better prognosis.